Joint characteristics of carbon steel bypass-current PAW on additive manufacturing. (January 2021) - Miao, Yugang; Li, Chunwang; Yin, Chenhao; Wei, Chao; Lin, Zhicheng
Highlights: Adjusting the bypass current can change the droplet transition mode. Larger bypass current can reduce the stirring force of the arc on the molten pool and improve the forming quality. Increasing the bypass current is conducive to smaller heat input and reducing the dilution rate of the base material. Abstract: In order to reduce heat input of the base metal, a novel process based on bypass-current plasma arc welding (BC-PAW) was proposed in this study to fabricate carbon steel thin-walled structures. The effects of bypass current on geometrical features, metal transfer behaviors, heat input and deposition efficiency were investigated in the single-layer deposition test. The multi-layer deposition test was carried out using appropriate process parameters, and the microstructure, hardness and mechanical properties of the deposited carbon steel were analyzed. Results show that the bypass current has a great influence on the transfer behaviors, which indirectly affects the bead appearance and geometrical features such as the beam width and fusion height. Keeping the total current constant, when the bypass current is increased, the heat input to the base material can be reduced and the melting efficiency of the wire can be increased at the same time. In the multi-layer deposition test, the differences in the location of each layer, the number of thermal cycles experienced, and the state of heat treatment make the results of solid phase transformation vary, forming a difference in microstructure. Due to the super-alloying of the bottom region, its hardness and tensile strength are greatest. It can be seen from the tensile fracture morphology that the test piece is ductile fracture.